PENGARUH DISIPLIN KERJA, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT PETROLOG INDAH BALIKPAPAN - Rahmawati Dewi Safitri1; Ariani, Misna; Yuliani, Tutik (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to determine the effect of work discipline, motivation, and work environment on job satisfaction of PT Petrolog Indah Balikpapan employees. This research was conducted at PT Petrolog Indah Balikpapan, with 44 respondents, this research method uses quantitative methods. Collecting data by means of observation and distributing questionnaires via google form. The data analysis technique used is multiple linier analysis by performing instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the variables of work discipline, motivation, and work environment had a positive and significant effect on job satisfaction